Analisis Blibiometrik Operating and Economic Exposure Dengan Publish or Perish dan VosViewer - Yudhi Prasetiyo; Wisnantiasri, Sila Ninin; Diky Paramitha; Elen Puspitasari (Universitas PGRI Yogyakarta, 2024)
This research aims to review comprehensive studies in an exploratory manner regarding operating exposure or economic exposure as an influence of fluctuations in the forex rate or foreign exchange rates on the present value of future cash flows in companies. The sample consists of 100 documents published in the period 2013 to 2023 using the crossref database with the keywords, forex rate, present value (PV), future value cash flow. This research conducted a systematic literature review using a bibliometric approach. Publish or perish and VOSviewer software were used to perform graphical analysis of bibliometric data and visualization of research results. Based on the visualization obtained, there are five types of colors as a clustering of links and relationships in terms of Operating Exposure which are searched in the database based on keywords. The first cluster is red which includes Indonesian stock exchange, earnings, stock price, value relevance, economic value. Then for the green cluster free cash flow and firm value. Then for the yellow cluster corporate governance, cash holding, and firm. Then for the light blue cluster, it is value and future direction. Then for the blue cluster it is rate, risk and overall tax advantages, and the last cluster in purple is net present value, return and cost. Bibliometric analytics can systematically review a number of studies to provide a less biased perspective. This also helps future research by combining research based on connectivity between keywords to better understand operating exposure in terms of company financial management.